ANALISA DAMPAK AKTIVITAS PENAMBANGAN PASIR TERHADAP KUALITAS FISIK AIR SUNGAI SERAYU DI KABUPATEN CILACAP - Rosita Dwityaningsih; Nurlinda Ayu Triwuri; Murni Handayani (Yayasan Akrab Pekanbaru, 2018)
Sand mining activities that continue to increase as a result of increasing demand for raw materials for infrastructure development have an impact on the environment. Negative impacts on the environment will occur if sand reduction can not be properly managed. One of the locations that is often used as a sand mining activity is the watershed. One of the river basin areas that contain sand mining activities is the Serayu DAS of Cilacap regency. In this research, the analysis of sand mining impact on physical quality of serayu river in Cilacap regency. Physical parameters measured were temperature, total dissolved solid (TDS) and electrical conductivity (DHL). The measurement results were conducted in 4 stations from upstream to downstream of Serayu River Cilacap Regency resulting temperature value of water between 30oC -31.5oC. The TDS value is in the range of 100 mg / L - 140 mg / L and the DHL value is in the range of 100 Î¼S / cm - 200 Î¼S / cm. Sand mining activities affect the rise of TDS and DHL in serayu river even though the value is still below the quality standard. Keywords: physical quality of river water, serayu river, sand mining